GAME EDUKATIF PENGENALAN BENDERA DAN IBUKOTA NEGARA DIASIA DAN EROPA MENGGUNAKAN CONSTRUCT2 - Aldi Ardiansyah Permana; Tri Ferga Prasetyo (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2022)
Games (Games) on mobile phones have now become an inseparable part, especially on the Android operating system. Most people, including students, spend a lot of time with cellphones for about 5-6 hours in front of cellphones just for applications and opening website addresses. The current digital era learning model has differences compared to conventional learning models. The PJJ model according to Azis (2019: 309) states that the digital era learning model consists of 3 models, first, the teacher provides online learning materials to students and then downloads and learns them manually (offline), both teachers provide online learning materials and participants students learn online too, and collaboration between learning that takes place between online and offline. The learning that has been carried out will end with an evaluation of both daily assessments, mid-semester assessments, and end-of-semester assessments. Based on the background above, the researchers intend to design applications that can be run via mobile phones with the Android operating system.